Prevalence, Correlates, and Outcomes of Omphalocele in the United States, 1995–2005. Issue 2 (August 2015) - Marshall, Jennifer; Salemi, Jason L.; Tanner, Jean Paul; Ramakrishnan, Rema; Feldkamp, Marcia L.; Marengo, Lisa K.; Meyer, Robert E.; Druschel, Charlotte M.; Rickard, Russel; Kirby, Russell S.
<x xml:space="preserve">Abstract</x> OBJECTIVE: To examine the trends in the prevalence, epidemiologic correlates, and 1-year survival of omphalocele using 1995–2005 data from the National Birth Defects Prevention Network in the United States. METHODS: We examined 2, 308 cases of omphalocele over 11 years from 12 state population-based birth defects registries. We used Poisson regression to estimate prevalence and risk factors for omphalocele and Kaplan-Meier survival curves and Cox proportional hazards regression to estimate survival patterns and hazard ratios, respectively, to examine isolated compared with nonisolated cases. RESULTS: Birth prevalence of omphalocele was 1.92 per 10, 000 live births with no consistent trend over time. Neonates with omphalocele were more likely to be male (prevalence ratio 1.22, 95% confidence interval [CI] 1.12–1.34), born to mothers 35 years of age or older (prevalence ratio 1.77, 95% CI 1.54–2.04) and younger than 20 years (prevalence ratio 1.34, 95% CI 1.14–1.56), and of multiple births (prevalence ratio 2.22, 95% CI 1.85–2.66). The highest proportion of neonates with omphalocele had congenital heart defects (32%). The infant mortality rate was 28.7%, with 75% of those occurring in the first 28 days. The best survival was for isolated cases and the worst for neonates with chromosomal defects (hazard ratio 7.75, 95% CI 5.40–11.10) and low-birth-weight neonates (hazard ratio 7.51, 95% CI 5.86–9.63). CONCLUSION: Prevalence of omphalocele has remained constant from 1995 to 2005. Maternal age (younger than 20 years and 35 years or older), multiple gestation, and male sex are important correlates of omphalocele, whereas co-occurrence with chromosomal defects and very low birth weight are consistent determinants of 1-year survival among these neonates. LEVEL OF EVIDENCE: II